Influencia de las Redes Sociales en el Rendimiento Académico de los alumnos del 5° grado del nivel secundario De la I.E. Aplicación N°0006 en la Provincia de Mariscal Cáceres – Juanjui - Cárdenas Ramírez, Constantin Eslavin (2013)
Social networking has revolutionized the relations not only between individuals But also between users and companies , public institutions and civil society platforms . The present project aimed to know the effects of the application of new information Technologies and communication in specific social networks in the teaching-learning Process , the study determined the influence of social networks in the academic Performance of students in the 5th grade I.e. Junior High Application No. 006 of the City of Juanjui , Mariscal Cáceres - San Martin. First, the most widely used social Network in the human target group study I investigate , then teaching materials were Designed , a group on the social network that was used as a platform for discussion And brainstorming forum was created in order to assist the understanding of texts of Different types, the critical opinion on the author's ideas and the language used , Yielding results in increased scores on the conceptual, procedural and attitudinal Performance ; overall academic performance using the social network in reading Comprehension is increased fair to good . The contribution of the research is that it Demonstrated that the social network can be used as a support tool in the teachinglearning Process of ongoing communication and implementation of this project the Principal, teachers and student of the institution were motivated education, to Implement icts in the teaching-learning process so that the project demonstrated its Sustainability over time.